China as a factor of international relations - Смaгуловa, К. К.; Абдыкaдыровa, А. Р.; Дaркенбaевa, К. К. (Journal of Oriental Studies, 2017)
In article the priority directions of foreign policy of Kazakhstan and a role of China in foreign policy of our republic are considered. Тhe article is devoted to the experience of China’s policy in the spheres of international economy and collective security within such organizations, as Shanghai Cooperation Organization. Is Chinese foreign policy concept in today’s era of globalization sustainable enough for it to become the world’s second superpower, whish directions form the basis of its promotion. Also, we can see the analysis of the methods which are used by Chinese government in such directions like USA, EU, Russia and the evolution of Chinese political, economic and financial relations with major powers of today.